Comparison of the Sensitivity of QuantiFERON-TB Gold In-Tube and T-SPOT.TB According to Patient Age - Bae, Won (Public Library of Science, 2016)
Currently, there are two types of interferon-gamma release assays (IGRAs) in use for the detection of tuberculosis (TB) infection, the QuantiFERON-TB Gold In-Tube test (GFT-GIT) and T-SPOT.TB. Owing to contradictory reports regarding whether the results of these IGRAs are affected by the age of the patient, we aimed to determine if these two tests have age-related differences in sensitivity. We retrospectively reviewed the medical records of diagnosed TB patients who were tested using either QFT-GIT or T-SPOT.TB from February 2008 to December 2013. The positivity of the two tests was analyzed and compared with true TB infection, which was defined as active TB based on either a positive Mycobacterium culture or a positive TB polymerase chain reaction. The QFT-GIT group included 192 TB patients, and the T-SPOT.TB group included 212 TB patients. Of the patients with pulmonary TB, 76 (39.6%) were in the QFT-GIT group and 143 (67.5%) in the T-SPOT.TB group. The overall sensitivity was 80.2% for QFT-GIT and 91.0% for T.SPOT.TB. The sensitivities of QFT-GIT and T-SPOT.TB according to age group were as follows: <29 years, 93.3% and 96.7%; 30–49 years, 86.5% and 94.7%; 50–69 years, 76.8% and 87.5%; and >70 years, 68.3% and 85.7%, respectively. The trend of age-related changes in sensitivity was significant for both QFT-GIT (p = 0.004) and T.SPOT.TB (p = 0.039). However, only QFT-GIT was significantly related to age in the multivariate analysis. QFT-GIT, but not T-SPOT.TB, was significantly affected by patient age.